ACTUALIZATION OF JAVANESE ECOCULTURE AND ISLAMIC ECOTHEOLOGY TOWARDS SUSTAINABLE DEVELOPMENT - Brontowiyono, Widodo (Universitas Islam Indonesia, 2019)
In line with development dynamics, environmental degradation continues and threatens development sustainability. The concept of sustainable development with economic, social, and environmental pillars requires actualization across aspects. Amongst the important aspects are culture and religion which is fundamentally inherent in every human being to drive behavior. The values of longstanding Javanese culture emphasize environmental conservation teachings, including Hamemayu Hayuning Bawono, Hamengku Buwono philosophy, Satriya attitude, and the forecasts saying kali ilang kedunge, pasar ilang kumandange, wong wadon ilang wirange, and wong lanang ilang kawibawane. Ecoculture actualization requires several strategies. First, the government policy should further consider environmental dynamics. Second, earth-related and environmental education should be intensified formally, informally, and non-formally. Third, the society should be informed and invited to actualize local wisdoms. Islamic values ​​should be further optimized as a fundamental strategy in environmental conservation. Islam views nature as Allah’s blessing, and the logical consequence is being grateful by continuously preserving it. Several important measures can promote ecological piety. First, Islamic education curriculum in boarding schools, madrasahs, Islamic forums, and formal schools should reinforce environmental theology and its applications. Second, religious organizations should facilitate intensive communication among stakeholders. Third, commitment is proven through tangible actions.